Peran Tafsir Tarbawi dalam Penguatan Etika Sosial di Lingkungan Pendidikan - Mirza, Iskandar; Anggraeni, Reni (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study aims to analyze the role of tafsir tarbawi in strengthening social ethics in Islamic educational environments. Using a descriptive qualitative method, this research examines the implementation of tafsir tarbawi in social ethics education through literature review, interviews with educators, and observations in Islamic educational settings. The results of the study indicate that the integration of tafsir tarbawi in education contributes significantly to the formation of students' character, especially in the aspects of justice, empathy, social responsibility, and noble ethics. However, there are challenges in its implementation, including the lack of teachers' understanding of the tafsir tarbawi concept, the scarcity of relevant teaching resources, and limited integration into the curriculum. Therefore, this study recommends strengthening teacher training, developing tafsir tarbawi-based teaching materials, and a more systematic integration into the curriculum to improve the effectiveness of social ethics education in Islamic educational environments.ABSTRAKPenelitian ini bertujuan untuk menganalisis peran tafsir tarbawi dalam penguatan etika sosial di lingkungan pendidikan Islam. Dengan menggunakan metode kualitatif deskriptif, penelitian ini mengkaji implementasi tafsir tarbawi dalam pembelajaran etika sosial melalui studi kepustakaan, wawancara dengan pendidik, serta observasi di lingkungan pendidikan Islam. Hasil penelitian menunjukkan bahwa integrasi tafsir tarbawi dalam pendidikan berkontribusi signifikan terhadap pembentukan karakter peserta didik, terutama dalam aspek keadilan, empati, tanggung jawab sosial, serta akhlak mulia. Namun, terdapat tantangan dalam implementasinya, termasuk kurangnya pemahaman guru terhadap konsep tafsir tarbawi, minimnya sumber ajar yang relevan, serta keterbatasan integrasi dalam kurikulum. Oleh karena itu, penelitian ini merekomendasikan penguatan pelatihan bagi pendidik, penyusunan bahan ajar berbasis tafsir tarbawi, serta integrasi yang lebih sistematis dalam kurikulum guna meningkatkan efektivitas pembelajaran etika sosial di lingkungan pendidikan Islam.